Perioperative complications following major vascular surgery. Correlations with preoperative clinical, electrocardiographic and echocardiographic features - Dimitri Tsialtas; Maria Giulia Bolognesi; Stephania Assimopoulos; Matteo Azzarone; Riccardo Volpi; Roberto Bolognesi (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: We investigated the incidence rate of perioperative complications following major vascular surgery, as well as identified the risk factors and preoperative clinical, electrocardiographic and echocardiographic determinants, related to these complications. Methods: We studied 241 patients with asymptomatic intact abdominal aortic aneurysm (AAA) subjected to open surgical repair, 182 with critical carotid stenosis subjected to endarterectomy (CEA), and 158 with severe symptomatic occlusive peripheral artery disease subjected to aortofemoral bypass (AFB). Preoperatively, all subjects provided a medical history and underwent physical, laboratory examinations, a standard ECG, and transthoracic echocardiography. Results: Overall, the perioperative mortality rate was 1.2%. The highest rate of complications was observed in the AAA group (p<0.01). Cardiac, respiratory, renal, gastrointestinal, and vascular complications were critically higher in the AAAs. Neurological complications were more common in the CEA compared to AAAs (p<0.01). Diabetic decompensation was more frequent in the AFB compared to the others (p<0.05). Mortality was correlated with left atrial enlargement and uricemia (p<0.03 respectively). Cardiac complications were correlated with heart rate (p<0.04), QT interval (p<0.001) and left ventricular mass (p<0.03), pulmonary with high levels of glycaemia (p<0.05) and overt diabetes (p<0.04), while renal insufficiency with hypertension (p<0.03), diabetes (p<0.01), previous myocardial infarction (p<0.01) and left anterior hemiblock (p<0.01), and neurological with hypertension (p<0.04) and overweight (p<0.01). Conclusions: We report a high rate of perioperative complications in vascular patients undergoing surgical revascularization. Cardiac, respiratory, renal, hematological, and gastrointestinal complications were predominant in the AAA group. Mortality appears significantly related to left atrial dimension and uricemia.